Negative electrode material, negative electrode sheet and secondary battery

By constructing a carbon coating layer with a specific lattice deviation on the surface of graphite negative materials, the problem of poor lithium and cycle performance of traditional graphite negative materials in the fast charge battery in the fast -charged battery is solved. And transmission efficiency and capacity improvement.

CN119381438APending Publication Date: 2025-01-28BTR NEW MATERIAL GRP CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411853429.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

Traditional graphite negative electrode materials have problems with interfacial lithium-ion and poor circulation performance in fast-charging battery applications, which limits their further applications.

Method used

The negative material including the kernel and the cover layer is used. The cover layer is composed of carbon materials, with multiple lattice stripes. Improve the adsorption and transmission capacity of lithium ions.

Benefits of technology

By introducing the defects of carbon materials, the adsorption capacity and transmission efficiency of the negative electrode materials on lithium ions are improved, and the interface dynamics and capacity are improved, while maintaining a lower surface area and a good first Kuron efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119381438A_ABST
    Figure CN119381438A_ABST
Patent Text Reader

Abstract

The invention relates to a negative electrode material, a negative electrode plate and a secondary battery, and provides a preparation method for realizing a controllable surface structure of the negative electrode material, the A value of the obtained negative electrode material is in a range of 10 to 35, and the deviation degree of a coating layer lattice of the negative electrode material and a graphitized lattice is in a proper degree; the performance indexes such as the capacity, the first coulombic efficiency and the multiplying power of a negative plate or a secondary battery applying the negative electrode material are in a relatively good range, and good comprehensive electrochemical performance is shown.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of electrochemical energy storage, and in particular to a negative electrode material, a negative electrode sheet and a secondary battery. Background Art

[0002] With the rapid increase in shipments and penetration of new energy vehicles, the market has increasingly stringent requirements on the performance of automotive power batteries. Fast charging performance is a key indicator of automotive power batteries, and the fast charging performance of power batteries is mainly determined by the fast charging performance of the negative electrode material at the material end. Graphite materials have become the mainstream choice in the current negative electrode material market due to their excellent processing performance and electrochemical stability.

[0003] However, when traditional graphite-based negative electrode materials are used as negative electrodes for fast-charging batteries, there are still problems such as interfacial lithium deposition and poor cycle performance, which hinder the further application of graphite-based negative electrode materials. Summary of the invention

[0004] In view of this, the present application provides a negative electrode material to solve at least one of the above problems.

[0005] To achieve the above-mentioned purpose, the present application provides a negative electrode material, comprising a core and a coating layer provided on at least a portion of the surface of the core, the coating layer comprising a carbon material, and in a transmission electron microscope photograph of the negative electrode material, the coating layer has a plurality of lattice stripes, a section of continuous straight lattice stripes formed by at least 5 atoms is selected as a reference lattice stripe, and a 3 nm×3 nm square area is selected in the transmission electron microscope photograph based on the reference lattice stripes, the reference lattice stripes are located in the square area, and a side length of the square area is parallel to the reference lattice stripes; the lattice stripes in the square area include a plurality of first lattice stripes, the first lattice stripes include at least 5 atoms, and at least a portion of the first lattice stripes has an angle of 3° to 15° with the reference lattice stripes, and the number of first lattice stripes is defined as A, 10≤A≤35.

[0006] In some possible implementations, the coating layer has a thickness of 3 nm to 50 nm.

[0007] In some possible implementations, the oil absorption value of the negative electrode material is 37 mL / 100 g to 47 mL / 100 g.

[0008] In some possible implementations, the negative electrode material has pores, and the volume of the pores with a pore diameter of 1.7 nm to 300 nm is less than 0.01 cm 3 / g.

[0009] In some possible implementations, the Raman scattering spectrum of the negative electrode material is at a wave number of 1350 ± 10 cm -1 and 1580±10 cm -1There are characteristic peaks D and G at the locations, and the ratio of the peak intensities of characteristic peaks D and G is I D / I G , I D / I G 0.25 to 0.50.

[0010] In some possible implementations, the core includes graphite, and the graphite includes at least one of natural graphite, artificial graphite, and microcrystalline graphite.

[0011] In some possible implementations, the median particle size D of the graphite particles is v 50 is 3 μm to 25 μm.

[0012] In some possible implementations, the fixed carbon content of the graphite is greater than or equal to 98%.

[0013] In some possible implementations, the specific surface area of ​​the negative electrode material is 1.2 m 2 / g to 4.3 m 2 / g.

[0014] In some possible implementations, the tap density of the negative electrode material is 0.90 g / mL to 1.15 g / mL.

[0015] The present application also provides a negative electrode sheet, comprising a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector, wherein the negative electrode active material layer comprises the above-mentioned negative electrode material.

[0016] The present application also provides a secondary battery, comprising the above-mentioned negative electrode sheet.

[0017] The present application characterizes the deviation of the coating layer lattice of the negative electrode material from the graphitized lattice through the A value. The larger the A value, the lower the degree of graphitization of the carbon material in the coating layer, and the higher the deviation of the coating layer lattice; compared with the core material with a straight and continuous lattice (such as layered graphite material), the discontinuous structure of the carbon material in the coating layer causes the lattice deviation on the surface of the negative electrode material to increase, resulting in distortion. The lattice distortion on the surface of the negative electrode material causes an increase in the number of defects on the basal plane perpendicular to the c-axis direction in the carbon material. Such defects are conducive to the adsorption and transmission of lithium ions and provide additional lithium storage sites; at the same time, the appropriate introduction of such defects will not lead to a significant increase in the specific surface area of ​​the material, which is conducive to maintaining a low specific surface area for the negative electrode material and maintaining a good first coulomb efficiency for the negative electrode material.

[0018] In the present application, when the A value meets the preset range, the carbon material contained in the coating layer of the negative electrode material may have a certain number of defects, so that the negative electrode material's adsorption capacity for lithium ions is improved, which is beneficial to the transmission of lithium ions in the negative electrode material, thereby helping to improve the interface dynamics; at the same time, such a coating layer can pre-store some lithium ions, and has the function of an ion pump, which is beneficial to the embedding dynamics transmission of lithium ions between the layers of the negative electrode material core (such as graphite), and the pre-stored lithium ions can also provide additional capacity contribution, which is beneficial to the improvement of the capacity of the negative electrode material. In addition, the defects of the carbon material are mainly located on the basal surface of the carbon material, so the defects will not cause a significant increase in the specific surface area of ​​the material, which is beneficial to maintaining the interface stability of the negative electrode material, and maintaining a small specific surface area, thereby improving the first coulomb efficiency of the negative electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 A schematic diagram of the structure of a secondary battery provided in one embodiment of the present application during charging.

[0020] Figure 2 A schematic diagram of the structure of a secondary battery provided in one embodiment of the present application during discharge.

[0021] Figure 3 A schematic diagram of the lattice structure of a carbon material for a secondary battery provided in one embodiment of the present application.

[0022] Figure 4 A transmission electron microscope image of the lattice structure of the negative electrode material provided in one embodiment of the present application.

[0023] Figure 5 for Figure 4 A locally enlarged schematic diagram of the lattice structure of the negative electrode material provided.

[0024] Figure 6 This is a scanning electron microscope image of the particle structure of the negative electrode material provided in Example 1 of the present application.

[0025] Figure 7 This is a transmission electron microscope image of the lattice structure of the negative electrode material provided in Example 1 of the present application.

[0026] Description of main component reference numerals: Electrode assembly, 100; positive electrode sheet, 101; negative electrode sheet, 102; isolation membrane, 103. DETAILED DESCRIPTION

[0027] The embodiments of the present application are described in detail below. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present application, and cannot be understood as limiting the present application; it should be noted that, unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by technicians in the technical field of the present application; in the absence of conflict, the embodiments of the present application and the features in the embodiments can be combined with each other; many specific details are elaborated in the following description to facilitate a full understanding of the present application, and the described embodiments are only part of the embodiments of the present application, not all of the embodiments.

[0028] In order to improve the fast charging performance of graphite negative electrode materials, researchers usually use material surface structure optimization strategies to improve interface transmission dynamics, thereby improving fast charging performance. For example, the authorized patent application CN113851725B achieves improved interface stability and improved transmission dynamics of graphite materials through electrolyte optimization, but the patent requires the optimization of electrolyte solvents, solutes and additives at the same time. The solute used is highly dangerous lithium perchlorate, and the rate improvement effect of graphite materials is limited. Authorized patent application CN111276674B uses carbon fluoride coating to achieve interface stability and dynamic improvement of graphite materials, but the material preparation in this patent involves solid-liquid mixing, hydrothermal reaction, solid-liquid separation, roasting and other steps. The process is complicated and the initial efficiency is low, and the industrial application value is low. Patent application CN117416955A uses inorganic metal oxide composite graphite materials, combined with high-energy ball milling, acid etching and resin coating to achieve material interface transmission dynamics and rate performance improvement. Although the fast charging performance of the patented material is significantly improved, the preparation method is too complicated and the production cost is high. It can be seen that the existing technology for coating the fast-charging graphite negative electrode has not yet achieved both precise control of the carbon structure on the material surface and low-cost process control.

[0029] The present application has found that the surface structure of graphite materials has an important influence on the lithium ion interface transport kinetics and fast charging performance. Based on this, the present application proposes a method for preparing a graphite negative electrode material with a controllable coating layer structure, which is beneficial to achieve precise control of the coating carbon layer structure in the negative electrode material and low-cost process control, thereby achieving the purpose of improving the reversible capacity and fast charging performance of the negative electrode material and reducing the process cost.

[0030] Based on this, an embodiment of the present application provides a secondary battery, comprising a housing, an electrode assembly and an electrolyte. The electrode assembly and the electrolyte are both located in the housing.

[0031] The outer shell may be a packaging bag encapsulated by an encapsulation film (such as an aluminum-plastic film), for example, a soft-pack battery. In other embodiments, it may also be a steel shell battery, an aluminum shell battery, etc.

[0032] See also Figure 1 and Figure 2The electrode assembly 100 includes a positive electrode sheet 101, a negative electrode sheet 102 and a separator 103. The separator 103 is disposed between the positive electrode sheet 101 and the negative electrode sheet 102. When an electrolyte (not shown) is provided, when charging, refer to Figure 1 , active ions (such as lithium ions) are deintercalated from the lattice of the positive electrode material (such as the lithiated intercalation compound) of the positive electrode sheet 101, pass through the separator 103 through the electrolyte, reach the negative electrode sheet 102 and insert into the lattice of the negative electrode material. Figure 2 , active ions (such as lithium ions) are deintercalated from the lattice of the negative electrode material of the negative electrode sheet 102, pass through the isolation membrane 103 through the electrolyte, reach the positive electrode sheet 101 and are embedded in the lattice of the positive electrode material (such as the lithiated intercalation compound), generating electrons that travel from the negative electrode sheet 102 through the external circuit to the positive electrode sheet 101, and the reverse movement of the electrons forms an electric current that can be used by electrical appliances.

[0033] In some embodiments, the electrode assembly 100 may be a laminated structure, which is formed by alternately stacking the positive electrode sheet 101, the separator 103, and the negative electrode sheet 102. In other embodiments, the electrode assembly 100 may also be a wound structure, which is formed by stacking the positive electrode sheet 101, the separator 103, and the negative electrode sheet 102 in sequence and then winding them.

[0034] Positive electrode The positive electrode sheet 101 includes a positive electrode current collector and a positive electrode material active layer provided on at least one surface of the positive electrode current collector. The positive electrode current collector may be made of aluminum foil or nickel foil, or may be any composite current collector disclosed in the prior art, such as but not limited to the current collector formed by combining the aforementioned conductive foil and a polymer substrate. The positive electrode material active layer includes a positive electrode active material, and the positive electrode active material includes a compound that can reversibly embed and deintercalate lithium ions (i.e., a lithiated intercalation compound). In some embodiments, the positive electrode active material may include a lithium transition metal composite oxide. The lithium transition metal composite oxide contains lithium and at least one element selected from cobalt, manganese and nickel. In some embodiments, the positive electrode active material may include but is not limited to lithium cobalt oxide (LiCoO2), lithium nickel manganese cobalt ternary material (NCM), lithium manganese oxide (LiMn2O4), lithium nickel manganese oxide (LiNi 0.5 Mn 1.5 O4) or at least one of lithium iron phosphate (LiFePO4).

[0035] The positive electrode material active layer also includes a binder to bond the positive electrode active material particles to facilitate the formation of a film layer, and at the same time, it can also improve the bonding force between the positive electrode material active layer and the positive electrode current collector. In some embodiments, the binder may include but is not limited to at least one of polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylic (ester) styrene-butadiene rubber, epoxy resin or nylon.

[0036] The positive electrode material active layer may also include a conductive material, including but not limited to a carbon-based material, a metal-based material, a conductive polymer, or any combination thereof. In some embodiments, the carbon-based material may include but is not limited to natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, or any combination thereof. In some embodiments, the metal-based material may include but is not limited to metal powder or metal fiber, such as copper, nickel, aluminum, or silver. In some embodiments, the conductive polymer may be a polyphenylene derivative.

[0037] Negative plate The negative electrode sheet 102 includes a negative electrode current collector and a negative electrode material active layer disposed on at least one surface of the negative electrode current collector. The negative electrode current collector may be at least one of copper foil, nickel foil, stainless steel foil, titanium foil or a carbon-based current collector, or may be any composite current collector disclosed in the prior art, such as but not limited to a current collector formed by combining the aforementioned conductive foil and a polymer substrate.

[0038] The negative electrode material active layer includes a negative electrode material, the negative electrode material includes a core and a coating layer disposed on at least part of the surface of the core, the coating layer includes a carbon material, in the transmission electron microscope photo of the negative electrode material, the coating layer has a plurality of lattice stripes, a continuous straight lattice stripe formed by at least 5 atoms is selected as a reference lattice stripe, and a 3 nm×3 nm square area is selected in the transmission electron microscope photo based on the reference lattice stripe, the reference lattice stripe is located in the square area, and the side length of the square area is parallel to the reference lattice stripe; the lattice stripes in the square area include a plurality of first lattice stripes, the first lattice stripes include at least 5 atoms, at least part of the first lattice stripes and the reference lattice stripes have an angle of 3° to 15°, and the number of the first lattice stripes is defined as A, 10≤A≤35. Wherein, the square area does not include the core; A can be 10, 12, 14, 15, 16, 17, 20, 22, 25, 26, 30, 35 or any value within the range formed by any two of the above values.

[0039] The present application uses the A value to characterize the deviation between the coating layer lattice and the graphitized lattice of the negative electrode material. The larger the A value, the lower the graphitization degree of the carbon material in the coating layer, and the higher the deviation of the coating layer lattice; compared with the core material with a straight and continuous lattice (such as layered graphite material), the discontinuous structure of the carbon material in the coating layer causes the lattice deviation of the negative electrode material surface to increase, resulting in distortion. Please refer to Figure 3 The lattice distortion on the surface of the negative electrode material causes an increase in the number of defects on the basal plane perpendicular to the c-axis in the carbon material. Such defects are beneficial to the adsorption and transmission of lithium ions and provide additional lithium storage sites. At the same time, the appropriate introduction of such defects will not lead to a significant increase in the specific surface area of ​​the material, which is beneficial for the negative electrode material to maintain a low specific surface area and to maintain a good first coulombic efficiency of the negative electrode material.

[0040] It should be noted that when calculating the A value in the set area, the angle between the lattice fringe to be observed and the reference lattice fringe is between 3° and 15° as the basis for counting. Figure 4 , select a 3 nm × 3 nm square area, see Figure 5 , in the enlarged area, the angle between the lattice fringes annotated as A+1 and the reference axis direction is between 3° and 15°, and the lattice fringes are included in the count of the A value, while the angle between the lattice fringes annotated as A+0 and the reference axis direction is greater than 15°, and the lattice fringes are not included in the count of the A value. The present application has found that the A value obtained based on the angle range can better obtain a negative electrode material with better performance. If the angle range is narrowed, the lattice fringes described by the A value tend to be parallel, and the obtained A value is not conducive to characterizing the deviation of the surface lattice of the negative electrode material. If the angle range is enlarged, the lattice fringes described by the A value tend to be more chaotic, which may cause the obtained negative electrode material that meets the preset range of the A value to have a too high disorder, resulting in defects at the end face of the coating layer carbon material, thereby increasing the specific surface area of ​​the negative electrode material and affecting the first coulomb efficiency.

[0041] In the present application, when the A value meets the preset range, the carbon material contained in the coating layer of the negative electrode material may have a certain number of defects, so that the adsorption capacity of the negative electrode material for lithium ions is improved, which is beneficial to the transmission of lithium ions in the negative electrode material, thereby improving the interface dynamics; at the same time, such a coating layer can pre-store some lithium ions, have the function of an ion pump, which is beneficial to the embedding dynamics transmission of lithium ions between the layers of the negative electrode material core (such as graphite), and the pre-stored lithium ions can also provide additional capacity contribution, which is beneficial to the improvement of the capacity of the negative electrode material. In addition, the defects of the carbon material are mainly located on the basal surface of the carbon material, so the defects will not cause a significant increase in the specific surface area of ​​the material, which is beneficial to maintaining the interface stability of the negative electrode material, and maintaining a small specific surface area, and improving the first coulomb efficiency of the negative electrode material. It can be understood that when the A value is lower than the lower limit, the surface lattice of the negative electrode material tends to be parallel, resulting in a low lattice deviation of the coating layer of the negative electrode material, which is not conducive to the generation of a sufficient number of defects, and the adsorption capacity of lithium ions is limited, which is not conducive to interface dynamics transmission and capacity improvement. When the A value is higher than the upper limit, the lattice of the negative electrode material coating tends to be chaotic, the coating is too disordered, or too many defects are generated at the end face of the carbon material, thereby increasing the specific surface area of ​​the negative electrode material, which is not conducive to the first coulomb efficiency.

[0042] In some embodiments, the thickness of the coating layer is 3 nm to 50 nm. For example, the thickness of the coating layer can be 3 nm, 6 nm, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 40 nm, 50 nm, or any value within the range formed by any two of the above values. Controlling the coating thickness of the negative electrode material within the above range is conducive to forming sufficient coverage on the surface of the negative electrode material core while maintaining good interface resistance and capacity. In some embodiments, the carbon coating layer can be a single-layer carbon coating layer formed by a single material, or a carbon coating layer formed by a combination of multiple materials, or a single material to form a multi-layer carbon coating layer, or a multi-layer carbon coating layer formed by multiple materials, etc. The layer structure of the carbon coating layer can be selected according to actual needs.

[0043] In some embodiments, the oil absorption value of the negative electrode material is 37 mL / 100 g to 47 mL / 100 g. For example, the oil absorption value of the negative electrode material can be 37 mL / 100 g, 38 mL / 100 g, 39 mL / 100 g, 40 mL / 100 g, 41 mL / 100 g, 42 mL / 100 g, 43 mL / 100 g, 44 mL / 100 g, 45 mL / 100 g, 46 mL / 100 g, 47 mL / 100 g, or any value within the range formed by any two of the above values. It should be noted that the oil absorption value of the negative electrode material is related to the gaps between the negative electrode material particles, the surface properties and the specific surface area, and the specific surface area of ​​the negative electrode material is related to the defects on the surface of the negative electrode material. Therefore, the oil absorption value of the negative electrode material is indirectly related to the surface defects of the negative electrode material. Therefore, controlling the oil absorption value of the negative electrode material within the above range can avoid slurry sedimentation, improve the stability of electrode coating, improve electrolyte infiltration, and also indicate that the negative electrode material has a suitable specific surface area and a suitable content of surface defects.

[0044] In some embodiments, the negative electrode material has pores, and the volume of the pores with a pore diameter of 1.7 nm to 300 nm is less than 0.01 cm 3 / g. The pore volume of the above pore size interval is within the preset range, indicating that a relatively uniform coating layer is provided on the surface of the negative electrode material, which results in fewer pores that can adsorb nitrogen during the pore volume test, such as when the pore volume is tested by nitrogen adsorption method, resulting in the above low value of the pore volume test result. The coating layer on the surface of the negative electrode material that meets the above pore volume characteristics is evenly distributed, which is beneficial to improving the stability of the surface structure of the negative electrode material, shortening the lithium ion transmission path, and effectively expanding the lithium ion transmission interface, thereby reducing the lithium ion transmission resistance, improving the lithium ion transmission efficiency, and improving the rate performance of the negative electrode material.

[0045] In some embodiments, the Raman scattering spectrum of the negative electrode material is at a wave number of 1350±10 cm -1 and 1580±10cm -1 There are characteristic peaks D and G at the locations, and the ratio of the peak intensities of characteristic peaks D and G is I D / I G , I D / I G is 0.25 to 0.50. For example, I D / I G It can be 0.25, 0.28, 0.32, 0.33, 0.35, 0.36, 0.37, 0.42, 0.50 or any value within the range formed by any two of the above values. D / I GReflects the disorder of the carbon material coated on the surface of the negative electrode material, I D / I G The above range indicates that the surface of the negative electrode material has suitable defects, which provides more active sites that are beneficial to the embedding of lithium ions, thereby improving the rate performance and reducing the expansion rate.

[0046] In some embodiments, the core includes graphite, and the graphite includes at least one of natural graphite, artificial graphite, and microcrystalline graphite. In some embodiments, the median particle size D of the graphite particles is v 50 is 3 μm to 25 μm. For example, the median particle size D of graphite particles is v 50 can be 3 μm, 8 μm, 10 μm, 15 μm, 20 μm, 25 μm, or any value within the range formed by any two of the above values. In some embodiments, the fixed carbon content of the graphite is greater than or equal to 98%. For example, the fixed carbon content of the graphite can be 98%, 98.5%, 99%, 99.5%, 99.9%, or any value within the range formed by any two of the above values.

[0047] In some embodiments, the specific surface area of ​​the negative electrode material is 1.2 m 2 / g to 4.3 m 2 / g. For example, the specific surface area of ​​the negative electrode material can be 1.2 m 2 / g, 1.6 m 2 / g, 2.1 m 2 / g, 2.3 m 2 / g, 2.6 m 2 / g, 2.7 m 2 / g, 2.9 m 2 / g, 3.2 m 2 / g, 3.8 m 2 / g, 4.3 m 2 / g or any value within the range formed by any two of the above values. It can be understood that the specific surface area of ​​the negative electrode material will affect the contact area between the negative electrode material and the electrolyte. The specific surface area of ​​the negative electrode material within the above range can reduce the amount of lithium ions consumed by the SEI film formed in the battery prepared by the negative electrode material during the first charge and discharge process, and reduce the irreversible capacity loss of the battery.

[0048] In some embodiments, the tap density of the negative electrode material is 0.90 g / mL to 1.15 g / mL. For example, the tap value of the negative electrode material can be 0.90, 0.95, 1.00, 1.03, 1.05, 1.06, 1.07, 1.09, 1.10, 1.12, 1.15, or any value within the range formed by any two of the above values. Controlling the tap density within the above range is conducive to forming a suitable compactness of the internal structure of the negative electrode material, thereby improving the transmission of lithium ions and the conduction of electrons, increasing the battery energy density, extending the cycle life, and improving safety performance.

[0049] The negative electrode material active layer also includes a binder to bind the negative electrode active material particles to facilitate the formation of a film layer, and can also improve the binding force between the negative electrode material active layer and the negative electrode current collector. In some embodiments, the binder may include but is not limited to polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene butadiene rubber, acrylic (ester) styrene butadiene rubber, epoxy resin or nylon, etc.

[0050] The negative electrode material active layer may also include a conductive material, including but not limited to a carbon-based material, a metal-based material, a conductive polymer, or any combination thereof. In some embodiments, the carbon-based material may include but is not limited to natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, or any combination thereof. In some embodiments, the metal-based material may include but is not limited to metal powder or metal fiber, such as copper, nickel, aluminum, or silver. In some embodiments, the conductive polymer may be a polyphenylene derivative.

[0051] Isolation film The isolation membrane 103 includes a membrane layer with a porous structure, and its material includes but is not limited to at least one of polyethylene, polypropylene, polyvinylidene fluoride, polyethylene terephthalate, polyimide or aramid. For example, the isolation membrane 103 can be a polypropylene porous membrane, a polyethylene porous membrane, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite membrane.

[0052] Electrolytes The electrolyte has the function of conducting ions between the positive electrode sheet 101 and the negative electrode sheet 102. The state of the electrolyte can be one or more of a gel state, a solid state and a liquid state. In some embodiments, the electrolyte is an electrolyte. The electrolyte plays the role of conducting active ions between the positive electrode sheet 101 and the negative electrode sheet 102. In some embodiments, the electrolyte includes a lithium salt and an organic solvent. The lithium salt can be selected from but not limited to one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium hexafluoroarsenate (LiAsF6), lithium perchlorate (LiClO4), lithium tetraphenylborate (LiB(C6H5)4), lithium methanesulfonate (LiCH3SO3), lithium bis(trifluoromethanesulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiCF3SO3), lithium bis(trifluoromethylsulfonyl)imide (LiN(SO2CF3)2, tris(trifluoromethylsulfonyl)methyl lithium (LiC(SO2CF3)3), lithium bis(oxalatoborate) (LiBOB) and lithium difluorophosphate (LiPO2F2). For example, the lithium salt is selected from LiPF6 because it can give high ionic conductivity and improve cycle characteristics. The organic solvent can be a carbonate compound, a carboxylate compound, an ether compound, Compounds, nitrile compounds, other organic solvents or combinations thereof. Examples of carbonate compounds include, but are not limited to, diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methylpropyl carbonate (MPC), ethylpropyl carbonate (EPC), ethylmethyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), vinylethylene carbonate (VEC), fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, trifluoromethylethylene carbonate or combinations thereof.

[0053] Another embodiment of the present application further provides a method for preparing a negative electrode material, comprising: The first step is to mix the crosslinking agent and graphite particles in liquid phase and dry them, wherein the feeding temperature of the drying is different from the discharging temperature of the drying, so as to obtain a first precursor.

[0054] In the above process, liquid phase mixing of the reactants helps to promote the mixing of graphite particles and crosslinking agents, and helps to effectively, fully and evenly react with subsequent reactants. At the same time, controlling the feed temperature and discharge temperature during drying to be different, providing a temperature difference at different stages of drying, helps to control the drying rate and maintain the morphology, structure and properties of the dried material.

[0055] In some embodiments, the cross-linking agent includes at least one of a compound containing iodide, sulfonate, borate, phosphate, aldehyde, sulfate and nitrate, such as ammonium iodide, sodium sulfonate, aminoethanesulfonic acid, phosphoric acid, diammonium phosphate, formaldehyde, terephthalaldehyde, glyoxal, sulfuric acid, sodium sulfate, nitric acid, etc.

[0056] In some embodiments, the feed temperature of the drying is higher than the discharge temperature. Controlling the feed temperature of the drying to be higher than the discharge temperature helps to continue drying the material with relatively less heat on the basis of providing a relatively large amount of heat for drying in the early stage, which helps to maintain the shape, structure and properties of the dried material and helps to better control the mixing ratio of the materials in the subsequent steps.

[0057] In some embodiments, the feed temperature of the drying is 200°C to 250°C, and the discharge temperature is 100°C to 150°C. For example, the feed temperature of the drying can be 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, or any value within the range formed by any two of the above values. The discharge temperature of the drying can be 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, or any value within the range formed by any two of the above values. Controlling the feed temperature and discharge temperature of the drying within the above ranges is conducive to maintaining the controllable morphology, structure and properties of the cross-linking agent and graphite particles after drying. Based on the controllable morphology, structure and properties, the mixing ratio between the subsequent materials can be better controlled, thereby achieving the purpose of controlling the disorder degree of the negative electrode material coating layer.

[0058] In some embodiments, liquid phase mixing includes mixing in a liquid phase solvent environment, and the liquid phase solvent includes at least one of deionized water, ethanol and methanol. Liquid phase mixing helps to promote the mixing of graphite particles and crosslinking agents, so during the liquid phase mixing process, the control of the solid-liquid ratio is based on ensuring that the graphite particles and the crosslinking agent can be normally stirred in the solvent, that is, the material is in a flowing and stirrable state.

[0059] Step 2: solid-phase mixing the first precursor with the coated carbon source, wherein the mass ratio of the cross-linking agent to the coated carbon source is (5-40):100, to obtain a second precursor. For example, the mass ratio of the cross-linking agent to the coated carbon source can be 5:100, 10:100, 15:100, 20:100, 25:100, 30:100, 35:100, 37.5:100, 40:100, or any value within the range of any two of the above values.

[0060] In the above process, the cross-linking agent used produces a cross-linking effect on the coated carbon source. Controlling the mass ratio of the cross-linking agent and the coated carbon source within the above range is beneficial to controlling the strength of the cross-linking effect of the cross-linking agent on the coated carbon source, and is beneficial to controlling the A value of the obtained negative electrode material; specifically, when the ratio is too high, the cross-linking effect of the cross-linking agent on the carbon source during the carbonization process is too strong, resulting in A>35. At this time, the disorder degree of the carbon coating is too high, resulting in an increase in the specific surface area of ​​the negative electrode material and a decrease in the first coulombic efficiency; when the ratio is too low, the cross-linking effect of the cross-linking agent on the carbon source during the carbonization process is relatively weak, resulting in A<10. At this time, the disorder degree of the carbon coating is too low, resulting in an increase in the interface impedance of the negative electrode material and poor fast charging performance.

[0061] In some embodiments, the mass ratio of the coated carbon source to the graphite is (2-25):100. For example, the mass ratio of the coated carbon source to the graphite can be 2:100, 4:100, 6:100, 8:100, 10:100, 12:100, 16:100, 20:100, 25:100, or any value within the range formed by any two of the above values. Controlling this ratio is conducive to forming a carbon coating layer of appropriate thickness on the surface of the core of the negative electrode material, providing sufficient surface coating for the core, and maintaining good interface resistance and capacity.

[0062] In some embodiments, the coated carbon source includes at least one of coal pitch, petroleum pitch, coal tar, and resin.

[0063] Step 3: heat-treating the second precursor, the heating rate of the heat treatment is 3°C / min to 10°C / min, and the temperature of the heat treatment is 1000°C to 1600°C, to obtain a negative electrode material. For example, the heating rate of the heat treatment can be 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min, or any value within the range of any two of the above values. The temperature of the heat treatment can be 1000°C, 1100°C, 1200°C, 1250°C, 1400°C, 1500°C, 1600°C, or any value within the range of any two of the above values.

[0064] In the above process, as the temperature rises, the cross-linking agent has a stronger catalytic effect on the coated carbon source, and the A value tends to increase; but the high temperature also causes the graphitization degree of the carbon derived from the coated carbon source to increase, causing the A value to tend to decrease; under the competition mechanism of the two factors, controlling the heat treatment temperature within the above range is conducive to controlling the A value within the range of 10 to 35, which is conducive to the negative electrode material showing better performance indicators. At the same time, controlling the appropriate heating rate is conducive to maintaining a stable reaction rate.

[0065] In some embodiments, the heat treatment is performed in a nitrogen, argon, or air atmosphere.

[0066] In some embodiments, the heat treatment holding time is 0.5 h to 6 h. For example, the heat treatment holding time can be 0.5 h, 1 h, 2 h, 2.5 h, 3 h, 4 h, 5 h, 6 h, or any value within the range of any two of the above values.

[0067] The scheme of the present application will be explained below in conjunction with the embodiments. Those skilled in the art will understand that the following examples are only used to explain the present application and cannot be construed as limiting the present application. Unless otherwise stated, the reagents, software and instruments not specifically stated in the following embodiments are all conventional commercial products or open source.

[0068] Embodiment 1: A negative electrode material, the preparation method of which comprises: S1, take 2 parts of phosphoric acid, 100 parts of graphite and 150 parts of deionized water, mix them evenly, control the feed temperature to 220° C., control the discharge temperature to 120° C., and perform spray drying to obtain a first precursor.

[0069] S2, 8 parts of asphalt and 100 parts of the first precursor were mixed in a VC mixer for 30 min to obtain a second precursor.

[0070] S3, under a nitrogen atmosphere, the second precursor is heated to 1250 °C at a heating rate of 6 °C / min and kept at this temperature for 4 h, then naturally cooled to below 200 °C and taken out to obtain the negative electrode material.

[0071] Embodiment 2: The difference from Example 1 is that in S1, phosphoric acid is replaced by ammonium iodide.

[0072] Embodiment 3: The difference from Example 1 is that in S1, phosphoric acid is replaced by formaldehyde.

[0073] Embodiment 4: The difference from Example 1 is that in S1, the amount of phosphoric acid is adjusted from 2 parts to 0.4 parts.

[0074] Embodiment 5: The difference from Example 1 is that in S1, the amount of phosphoric acid is adjusted from 2 parts to 1.2 parts.

[0075] Embodiment 6: The difference from Example 1 is that in S1, the amount of phosphoric acid is adjusted from 2 parts to 2.8 parts.

[0076] Embodiment 7: The difference from Example 1 is that in S2, the amount of asphalt is adjusted from 8 parts to 4 parts; at the same time, the amount of phosphoric acid in S1 is adjusted from 2 parts to 1 part to keep the ratio of asphalt to phosphoric acid unchanged.

[0077] Embodiment 8: The difference from Example 1 is that in S2, the amount of asphalt is adjusted from 8 parts to 12 parts; at the same time, the amount of phosphoric acid in S1 is adjusted from 2 parts to 3 parts to keep the ratio of asphalt to phosphoric acid unchanged.

[0078] Embodiment 9: The difference from Example 1 is that in S2, the amount of asphalt is adjusted from 8 parts to 20 parts; at the same time, the amount of phosphoric acid in S1 is adjusted from 2 parts to 5 parts to keep the ratio of asphalt to phosphoric acid unchanged.

[0079] Embodiment 10: The difference from Example 1 is that in S3, the nitrogen atmosphere is adjusted to an argon atmosphere.

[0080] Embodiment 11: The difference from Example 1 is that in S3, the heating temperature of the second precursor is adjusted from 1250°C to 1000°C.

[0081] Embodiment 12: The difference from Example 1 is that in S3, the heating temperature of the second precursor is adjusted from 1250°C to 1600°C.

[0082] Comparative Example 1: The difference from Example 1 is that in S1, no deionized water is added, that is, 2 parts of phosphoric acid and 100 parts of graphite are directly uniformly mixed and spray-dried.

[0083] Comparative Example 2: The difference from Example 1 is that in S1, the amount of phosphoric acid is adjusted from 2 parts to 5 parts.

[0084] Comparative Example 3: The difference from Example 1 is that in S3, the heating temperature of the second precursor is adjusted from 1250°C to 2000°C.

[0085] Taking Example 1 as an example, the microscopic morphology of the surface of the obtained negative electrode material was observed using a HITACHI-S4800 scanning electron microscope; the specific steps include sticking the conductive glue on the sample cup, evenly coating the sample on the conductive glue, using an ear-cleaning bulb to blow away the loose sample, and placing it in the scanning electron microscope room for testing. Figure 6Taking the two selected fields of view (a) and (b) as examples, the negative electrode material prepared in the embodiment of the present application has a spherical morphology as a whole, and there are no obvious agglomerates, indicating that the preparation method of the present application can achieve uniform distribution of the coating on the graphite material.

[0086] Taking Example 1 as an example, the morphology of the sample coating layer was observed using a Talos F200S electron microscope, and the acceleration voltage during the test was 200 kV; the specific steps included taking an appropriate amount of graphite powder to be tested and ethanol and adding them to a mortar, grinding them manually for 5 minutes, and then ultrasonically oscillating them for 20 minutes, taking an appropriate amount of a uniform mixture of powder and ethanol, and dropping 2 to 3 drops of the mixed liquid on the microgrid. Please refer to Figure 7 The negative electrode material prepared in the embodiment of the present application shows obvious core-shell structural characteristics under a high-magnification transmission electron microscope, wherein the lattice fringes in the core region are regularly, straightly and neatly arranged, while the lattice fringes in the shell region show a discontinuous structure.

[0087] The physical and electrochemical properties of the negative electrode materials obtained in the above examples 1-12 and comparative examples 1-3 were tested, and the testing methods were as follows: 1. A value test of negative electrode material: Take an appropriate amount of graphite powder and ethanol to be tested and add them to the mortar respectively. After manual grinding for 5 minutes, ultrasonic oscillate for 20 minutes. Take an appropriate amount of powder and ethanol uniform mixture, and drop 2 to 3 drops of the mixed liquid on the microgrid. Use Talos F200S electron microscope to observe the morphology of the sample coating layer, and the acceleration voltage during the test is 200 kV. Under the TEM field of view, select the area where the surface coating layer can be clearly observed, measure the thickness of the coating layer, and take the corresponding picture at an appropriate magnification (the scale of the electron microscope ruler is 5 nm to 20 nm at this time). Take a TEM picture, pull out a 3 nm×3 nm square area from the direction parallel to the disordered carbon lattice, take an edge parallel to the direction of the disordered carbon lattice, and in the square area, the total number of disordered carbon lattice fringes with an angle less than 15° with the edge is the A value.

[0088] 2. Oil absorption value test: Determine in accordance with GB / T 3780.2-2017 "Carbon black part 2: determination of oil absorption value"; a certain mass of powder sample is placed in the mixing chamber, and then linseed oil is dripped on the sample at a constant speed and stirred simultaneously with two motor-driven rotating wings. As the sample absorbs more linseed oil, the mixture changes from a free-flowing state to a semi-plastic agglomerate. During this process, the viscosity of the mixture gradually increases and a peak value appears. The measurement endpoint is the amount of linseed oil dripped when the torque generated by the change in viscosity characteristics reaches the set value or a constant percentage of the maximum torque obtained from the torque curve, and the oil absorption value of the sample to linseed oil (mL / 100g) is calculated.

[0089] 3. Pore volume test: The volume of pores with a pore size of 1.7 nm to 300 nm was tested by gas adsorption method (nitrogen adsorption multi-point BET) at low temperature controlled by liquid nitrogen using the American Micromeritics TriStar 3000 & 3020 specific surface area and pore size analyzer.

[0090] 4. Raman I D / I G Test: The Raman scattering spectrum was tested using a HORIBA-XPLORA laser confocal Raman spectrometer with a laser wavelength of 532 nm. 30 points were taken for each sample for data collection, and the scattering spectrum obtained at each point was then peak fitted. The peak position of material D was 1350 cm -1 The G peak is located at 1580 cm -1 After marking the D and G peaks, the D / G peak intensity ratio is calculated as I D / I G value.

[0091] 5. Particle size test of negative electrode materials: The particle size distribution range of negative electrode materials was tested by Malvern 3000 laser particle size analyzer. Dispersant (ethanol, pure water and low foaming surfactant) and the test sample were placed in a 50 mL beaker, and a certain amount of pure water was added. The sample was fully stirred with a glass rod to disperse the sample evenly. The equipment pump speed was set to 2400 r / min to 2500 r / min and the frequency was 19.5 Hz for particle size test. Median particle size D v 50 refers to the particle size value corresponding to the cumulative distribution percentage of volume ratio reaching 50%.

[0092] 6. Specific surface area test of negative electrode materials: Use the precision micro-Gaobo DX400 to test the specific surface area of ​​materials, put the sample into the sample tube, use the isothermal jacket on the sample tube, put the filling rod into the bubble tube, install the clamp ring and O-ring on the bubble tube, and then put the assembled sample bubble tube into the corresponding analysis station for testing. Under constant temperature and low temperature, after measuring the adsorption amount of gas on the solid surface at different relative pressures, the adsorption amount of the sample monolayer is obtained based on the Brown-Ett-Taylor adsorption theory and its formula (BET formula), so as to calculate the specific surface area of ​​the material.

[0093] 7. Tap density test of negative electrode materials: Use the Quantachrome DAT-6-220 tap density tester to place a sample of specified mass in a measuring cylinder, vibrate it for a specified number of times (1000 times for conventional testing), read the volume of the measuring cylinder after tapping and calculate the tap density.

[0094] 8. Electrochemical performance test: The negative electrode materials prepared in the examples and comparative examples were dissolved in N-methylpyrrolidone according to the mass ratio of 96.5:1.5:1 negative electrode materials, carboxymethyl cellulose and styrene-butadiene rubber, respectively, and the solid content was controlled to be 50%. The negative electrode sheets were coated on copper foil current collectors, vacuum dried, rolled and punched to obtain negative electrode sheets. Metal lithium sheets were used as counter electrodes and assembled into button cells in a glove box filled with argon. At a current density of 0.1 C, charge and discharge tests were performed in the charge and discharge range of 0.01 V to 1.5 V to obtain the first reversible specific capacity, first cycle charge capacity and first cycle discharge capacity. The first coulomb efficiency = first cycle discharge capacity / first cycle charge capacity; after completing the above tests, the charging current density was 0.2 C, and the discharge lithium insertion test was performed at current densities of 0.2 C, 0.5 C, 1 C, and 2 C, respectively. The 2 C / 0.2 C rate performance = 0.2 C discharge lithium insertion capacity / 2 C discharge lithium insertion capacity.

[0095] Please refer to Table 1 for some of the preparation conditions of the above Examples 1-12 and Comparative Examples 1-3, and please refer to Table 2 for the above test results.

[0096] Table 1. Partial preparation conditions of Examples 1-12 and Comparative Examples 1-3 of the present application Table 2. Performance test results of Examples 1-12 and Comparative Examples 1-3 of the present application Under the preparation process conditions of the present application, the negative electrode materials of Examples 1-12 are provided with a carbon coating layer on the surface of the core, and the lattice fringes present a discontinuous structure, which leads to an increase in the lattice deviation on the surface of the negative electrode material, resulting in distortion, and having an A value within a preset range, that is, a suitable number of specific lattices, such that the lattice can introduce suitable defects on the basal plane of the carbon material, so that the negative electrode material has a higher lithium ion adsorption capacity, improves the electrolyte infiltration and interface kinetic transmission performance of the negative electrode material, and improves the rate performance; at the same time, the defects can also pre-store some lithium ions, have the function of ion pumps, and improve the embedding kinetic transmission of lithium ions between graphite layers. The pre-stored lithium ions can also provide additional capacity contribution, thereby improving the capacity of the negative electrode material. Moreover, such a lattice will not lead to a significant increase in the defects on the end faces of the carbon material, thereby maintaining a low specific surface area and a good first coulomb efficiency for the negative electrode material.

[0097] Compared with Example 1, Comparative Example 1 did not use a liquid phase mixing method during the mixing process of the cross-linking agent and graphite, resulting in poor mixing uniformity. In the subsequent carbon source coating and carbonization process, the cross-linking catalytic effect of the cross-linking agent on the coated carbon source was uneven, resulting in poor material rate performance and low practicality.

[0098] Compared with Example 1, the proportion of cross-linking agent added in Example 2 is too high. At this time, material A is greater than 35. The excessively large A value causes a large deviation of the surface lattice of the negative electrode material. At this time, defects may also occur at the end faces of the carbon material of the negative electrode material coating layer, thereby increasing the specific surface area of ​​the negative electrode material and reducing the initial coulombic efficiency.

[0099] Compared with Example 1, the carbonization temperature of Comparative Example 3 is relatively high. At this time, material A is less than 10. The small A value indicates that the surface lattice of the negative electrode material tends to be flat and continuous, the surface defects of the negative electrode material are insufficient, and the adsorption capacity of lithium ions is limited, resulting in reduced lithium insertion amount and reduced capacity; at the same time, the surface defects of the negative electrode material are insufficient, which affects the interface kinetic transmission performance, resulting in reduced rate performance.

[0100] In summary, the present application provides a graphite negative electrode material with controllable surface structure, a preparation method and a lithium-ion battery thereof. The preparation method in the present application can achieve an A value in the range of 10 to 35, and the deviation of the lattice of the corresponding material coating layer is at an appropriate level. At the same time, the performance indicators such as the capacity, first efficiency, and rate of the negative electrode material are all in a better range, showing good comprehensive electrochemical performance.

[0101] The above implementation modes are only used to illustrate the technical solutions of the present application and are not intended to limit the present application. Although the present application has been described in detail with reference to the above preferred implementation modes, a person skilled in the art should understand that the technical solutions of the present application may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present application.

Claims

1. A negative electrode material, comprising a core and a coating layer disposed on at least a portion of the surface of the core, characterized in that: The coating layer includes a carbon material. In a transmission electron microscope photograph of the negative electrode material, the coating layer has a plurality of lattice fringes. A continuous straight lattice fringes formed by at least 5 atoms are selected as reference lattice fringes. A square area of ​​3 nm×3 nm is selected in the transmission electron microscope photograph based on the reference lattice fringes. The reference lattice fringes are located in the square area, and the length of one side of the square area is parallel to the reference lattice fringes. The lattice fringes within the square area include multiple first lattice fringes, the first lattice fringes include at least 5 atoms, and the angle between at least part of the first lattice fringes and the reference lattice fringes is 3° to 15°. The number of the first lattice fringes is defined as A, 10≤A≤35.

2. The negative electrode material according to claim 1, characterized in that The coating layer has a thickness of 3 nm to 50 nm.

3. The negative electrode material according to claim 1, characterized in that The oil absorption value of the negative electrode material is 37 mL / 100 g to 47 mL / 100 g.

4. The negative electrode material according to claim 1, characterized in that The negative electrode material has pores, and the volume of the pores with a pore diameter of 1.7 nm to 300 nm is less than 0.01 cm 3 / g.

5. The negative electrode material according to claim 1, characterized in that The Raman scattering spectrum of the negative electrode material is at a wave number of 1350±10 cm -1 and 1580±10 cm -1 There are characteristic peaks D and G at the locations thereof, respectively, and the ratio of the peak intensities of the characteristic peaks D and G is 1 D / I G , I D / I G 0.25 to 0.

50.

6. The negative electrode material according to claim 1, characterized in that The core includes graphite, and the negative electrode material further satisfies at least one of the following conditions: (1) The graphite includes at least one of natural graphite, artificial graphite and microcrystalline graphite; (2) The median particle size D of the graphite particles v 50: 3 μm to 25 μm; (3) The fixed carbon content of the graphite is greater than or equal to 98%.

7. The negative electrode material according to claim 1, characterized in that The specific surface area of ​​the negative electrode material is 1.2 m 2 / g to 4.3 m 2 / g.

8. The negative electrode material according to claim 1, characterized in that The tap density of the negative electrode material is 0.90 g / mL to 1.15 g / mL.

9. A negative electrode sheet, comprising a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector, characterized in that: The negative electrode active material layer comprises the negative electrode material according to any one of claims 1 to 8.

10. A secondary battery, characterized in that: Comprising the negative electrode sheet as claimed in claim 9.

Citation Information

Patent Citations

  • A modified graphite anode material, its preparation method, and a battery containing the modified graphite anode.

    CN111276674B

  • A fast-charging electrolyte and its application

    CN113851725B

  • Graphite negative electrode material precursor, graphite negative electrode material as well as preparation method and application of graphite negative electrode material

    CN117416955A